Black and yellow lichen moth (suggested common name) Lycomorpha pholus (Drury) (Insecta: Lepidoptera: Noctuidae: Arctiinae: Lithosiini) - Clare Scott (EDIS)
EENY479, a 5-page illustrated fact sheet by Clare Scott, is part of the Featured Creatures collection. It describes this lichen moth common in the Neotropics — synonymy, distribution, description, life cycle, hosts, and mimicry. Includes references. Published by the UF Department of Entomology and Nematology, August 2010.